AIAA Modeling and Simulation Technologies Conference 2017
DOI: 10.2514/6.2017-3473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motion Cues on the Training of Multi-Axis Manual Control Skills

Abstract: The study described in this paper investigated the effects of two different hexapod motion configurations on the training and transfer of training of a simultaneous roll and pitch control task. Pilots were divided between two groups which trained either under a baseline hexapod motion condition, with motion typically provided by current training simulators, or an optimized hexapod motion condition, with increased fidelity of the motion cues most relevant for the task. All pilots transferred to the same full-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 18 publications
5
21
0
Order By: Relevance
“…They were chosen to fully cover the range of human control at regular intervals on a logarithmic scale. 20 The amplitudes of the sinusoids were determined using a second-order low-pass filter. The amplitudes of the first four sine waves were manually changed in order to keep the aircraft elevator and aileron deflections within their maximum deflections and the motion of the simulator within the boundaries of the motion envelope throughout the stall task.…”
Section: Forcing Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…They were chosen to fully cover the range of human control at regular intervals on a logarithmic scale. 20 The amplitudes of the sinusoids were determined using a second-order low-pass filter. The amplitudes of the first four sine waves were manually changed in order to keep the aircraft elevator and aileron deflections within their maximum deflections and the motion of the simulator within the boundaries of the motion envelope throughout the stall task.…”
Section: Forcing Functionsmentioning
confidence: 99%
“…For roll the variance was higher, 5.0 deg 2 , since it was found that the roll error was more difficult to perceive on the PFD. 20 To determine the phase distributions, a high number of phase sets was randomly generated. Two sets were selected that created signals with a Gaussian-like distribution and an average crest factor.…”
Section: Forcing Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, in order to train pilots efficiently, flight simulators are designed to present pilots with high fidelity simulation cues, 3 such as motion cues. However, even though the benefit of using motion-enabled flight simulators in the training of pilot control skills is the subject of much debate, [4][5][6][7] current pilot training requirements still focus heavily on the availability of motion in flight simulators. The focus on motion is even growing, which is illustrated by the new requirement for airline pilots to receive stall training in full-motion flight simulators starting in 2019.…”
Section: Introductionmentioning
confidence: 99%